Relationship Between Spiritual Care Needs and Cognitive Intrusion of Pain in Patients with Advanced-Stage Cancer in Türkiye - Türkben Polat, Hilal (Journal of religion and health, 2025)
Pain is a common symptom experienced by patients with advanced-stage cancers. This research was conducted to determine the relationship between spiritual care needs and the cognitive intrusion of pain in patients with advanced-stage cancer. The data were collected through the patient information form, visual pain scale (VPS), spiritual care needs scale (SCNS), and cognitive intrusion of pain scale (CIPS). The study was conducted with 138 advanced cancer patients. Patients had a moderate level of spiritual care needs and an above moderate level of cognitive intrusion of pain. A positive correlation was found between the total CIPS score and the meaning and hope subdimension score of SCNS (p = 0.022). Cognitive intrusion of pain increased as the need for meaning and hope in spiritual care increased. In conclusion, meeting the spiritual care needs of patients is important to prevent patients from focusing excessively on the pain they are experiencing.